Complex mosaic CDKL5 deletion with two distinct mutant alleles in a 4‐year‐old girl. Issue 8 (8th April 2014) - Boutry‐Kryza, Nadia; Ville, Dorothée; Labalme, Audrey; Calender, Alain; Dupont, Jean‐Michel; Touraine, Renaud; Edery, Patrick; des Portes, Vincent; Sanlaville, Damien; Lesca, Gaetan
<x xml:space="preserve">Abstract</x> Mutations of the CDKL5 gene cause early epileptic encephalopathy. Patients manifest refractory epilepsy, beginning before the age of 3 months, which is associated with severe psychomotor delay and features that overlap with Rett syndrome. We report here a patient with mosaicism for CDKL5 exonic deletion, with the presence of two mutant alleles. The affected 4‐year‐old girl presented with infantile spasms, beginning at the age of 9 months, but subsequent progression of the disease was consistent with the classical CDKL5‐related phenotype. A deletion of exons 17 and 18 was suspected on the basis of Multiplex Ligation Probe Amplification analysis, but unexpected results for cDNA analysis, which showed the presence of an abnormal transcript with the deletion of exon 18 only, led us to suspect that two distinct events might have occurred. We used custom array‐CGH to determine the size and breakpoints of these deletions. Exon 18 was deleted from one of the abnormal alleles, and exon 17 was deleted from the other. A Fork Stalling and Template Switching (FoSTeS) mechanism was proposed to explain the two events, given the presence of regions of microhomology at the breakpoints. We propose here an original involvement of the FoSTeS mechanism to explain the co‐occurrence of these two events in the CDKL5 gene in a single patient. This patient highlights the difficulties involved in the detection of such abnormalities, particularly when they occur in a mosaic state and involve two distinct mutational events in a single gene. © 2014 Wiley Periodicals, Inc.